2019
DOI: 10.1128/jb.00731-18
|View full text |Cite
|
Sign up to set email alerts
|

Entry Exclusion of Conjugative Plasmids of the IncA, IncC, and Related Untyped Incompatibility Groups

Abstract: Conjugative plasmids of incompatibility group C (IncC), formerly known as A/C 2 , disseminate antibiotic resistance genes globally in diverse pathogenic species of Gammaproteobacteria. Salmonella genomic island 1 (SGI1) can be mobilized by IncC plasmids and was recently shown to reshape the conjugative type IV secretion system (T4SS) encoded by these plasmids to evade entry exclusion. Entry exclusion blocks DNA translocation between cells containing identical or highly similar plasmids. Here, we report that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 63 publications
0
41
0
Order By: Relevance
“…Although probably unable to activate self-transfer, entry of SGI1 in the host could resuscitate such "zombie" plasmids that would transiently regain their capacity to transfer, and mediate mobilisation of SGI1 (Supplementary Figure S6). This process would be facilitated by the ability of SGI1 to escape entry exclusion exerted by IncA and IncC plasmids that normally prevents or strongly reduces redundant transfer between cells that contain plasmids of the same entry exclusion group (31,38). Figure 1A), we propose that an IncC plasmid-encoded factor, triggers a positive feed-back loop in response to low levels of SgaCD likely via activation of sgaDC expression.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although probably unable to activate self-transfer, entry of SGI1 in the host could resuscitate such "zombie" plasmids that would transiently regain their capacity to transfer, and mediate mobilisation of SGI1 (Supplementary Figure S6). This process would be facilitated by the ability of SGI1 to escape entry exclusion exerted by IncA and IncC plasmids that normally prevents or strongly reduces redundant transfer between cells that contain plasmids of the same entry exclusion group (31,38). Figure 1A), we propose that an IncC plasmid-encoded factor, triggers a positive feed-back loop in response to low levels of SgaCD likely via activation of sgaDC expression.…”
Section: Discussionmentioning
confidence: 95%
“…Oligonucleotides used in this study are listed in Supplementary Table S1. New sequencing data obtained from pVCR94 (NZ_CP033514.1) revealed that pVCR94 Sp (38) was missing eight conserved IncC genes. Therefore a new derivative, pVCR94 Sp2 , was constructed using the one-step chromosomal gene inactivation technique with pMS1, primer pair pVCR94delY2.f/94DelXnoFRT.rev and pVI36 as the template (39).…”
Section: Plasmids and Strains Constructionsmentioning
confidence: 99%
“…All transpovirons encode a short predicted membrane protein although their primary sequence does appear to be conserved. The dominance effect is reminiscent of plasmids incompatibility or entry exclusion for related plasmids [60][61][62][63] or superinfection immunity [64] and superinfection exclusion [65] used by prophages to prevent superinfection by other bacteriophages. For the latter, DNA injection is often inhibited by a membrane-bound protein [66][67][68], paralleling the eventual role of the transpoviron-encoded membrane protein in giant virus particles carrying a transpoviron.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence of this short protein is not conserved between transpovirons associated to different host virus clades but all transpovirons encode such predicted membrane protein. The dominance effect is reminiscent of plasmids incompatibility or entry exclusion for related plasmids (3538) or superinfection immunity (39) and superinfection exclusion (40) used by prophages to prevent superinfection by other bacteriophages. For the latter, DNA-injection is inhibited by a membrane-bound protein (4143), paralleling the eventual role of the transpoviron-encoded membrane protein in giant virus particles carrying a transpoviron.…”
Section: Discussionmentioning
confidence: 99%